Structural holes, knowledge intermediaries and evolution of the triple helix system with reference to the hard disk drive industry in Thailand. (1st March 2015) - Nakwa, Karantarat; Zawdie, Girma
This article explores the evolutionary process underlying the development of the triple helix innovation system and the role of knowledge intermediaries in the process. It draws on the experience of knowledge network development in an SME cluster in the Thai hard disk drive industry. Conceptually, the evolutionary process starts with inter-firm networks, which occur in the form of supply chain-based vertical links and trade association or cluster-based horizontal links. These evolve into triple helix networks and culminate into the triple helix innovation system through the agency of network dynamics. Intermediaries enhance network development as sponsors, providing funds; as brokers, closing and bridging structural holes that disconnect network players; and as boundary spanners, facilitating knowledge circulation. The case study suggests that knowledge network development in Thailand has a long way to go before morphing into the triple helix innovation system. Some evidence of network dynamics was nonetheless detected; but for lack of trust in the triple helix culture the fledgling network dynamics fizzled out when the government prop, which initiated the process, was withdrawn. The article concludes by highlighting the need for policy to promote the culture of trust among network players and for knowledge intermediaries to be robustly systemic in their organization and operation.